Synthesis and some properties of new functionally substituted poly-5-vinyltetrazoles - Grigoriev, Yuri V.; Shiman, Dmitriy I.; Grigorieva, Inna M.; Abramovich, Ekaterina A.; Kosterova, Darya S.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2025)
It was found that the solubility of poly-5-vinyltetrazole in organic solvents can be extended by its reprecipitation from dimethylformamide solutions into trifluoroacetic acid, as well as into a mixture of carboxylic acids with diethyl ether, acetone or tetrahydrofuran. Methods for the preparation of N-alkyl-poly-5-vinyltetrazoles have been proposed. It has been found that the introduction of an n-alkyl substituent into the tetrazole fragment of poly-5-vinyltetrazole leads to increasing of solubility of resulted polymers in a wide range of organic solvents, while glass transition temperature of polymers decreases with increasing length of the hydrocarbon substituent. A method for the synthesis of new poly-5-vinyltetrazole derivatives containing both N-methylated and N, N′-dimethyl (quaternised) has been developed, which give possibility to obtain polymers with adjustable ratio of methylated and quaternised tetrazole cycles. It was shown that the value of specific heat of thermal decomposition of N, N′-dimethyl-poly-5-vinyltetrazolium perchlorates increases with growing degree of quaternisation. The results of these studies can be used for the synthesis of N-substituted poly-5-vinyltetrazoles with desired structure and physico-chemical properties.